REKONSTRUKSI PARADIGMA PENANGGULANGAN STUNTING : INTERNALISASI NILAI-NILAI QUR’ANI SEBAGAI UPAYA PENGUATAN MORAL ORANG TUA - Maudy Muzalifah Azzahra; Bashori (PT. Hasba Edukasi Mandiri, 2026)
Stunting remains a crucial challenge for human resource development in Indonesia, despite the massive implementation of various medical technocratic policies. The low effectiveness of nutritional interventions in the field is often triggered by sociocultural factors and a lack of profound parental awareness regarding children's developmental rights. This study aims to reconstruct the stunting prevention paradigm through an Islamic theological approach by internalizing Quranic values as a basis for parenting motivation. Employing a descriptive qualitative method with a literature study and thematic exegesis (tafsir) approach, this research proposes the concept of